Evaluation of Two Dental Digital Imaging Systems Based on Quality Scorings, Burn-Out Effects and Cervical Width Determination - Aydin Kader Cesur; Demirel Oğuzhan; Salli Gülay Altan; Özcan Mutlu (Balkan Stomatological Society, 2020)
Background/Aim: The aim of the present study is to evaluate diagnostic accuracy of two generic image receptors with CMOS and PSP sensors for image quality scoring (IQS), burnout incidences (BI) and cervical widths (CW) with regard to four different exposure times.